Representaciones sociales del ejercicio de la sexualidad en estudiantes de universidades privadas de Lima Metropolitana - Diaz Tahua, Andrea Lucia (2024)
The objective of this research was to explore the social representations about the exercise of sexuality in young students of private universities in Metropolitan Lima. A qualitative approach was used to explore the aforementioned constructs, with a thematic analysis design. The participants were eight students from a private university, four graphic design students, three performing arts students and one textile design student. There were an equal number of male and female participants. An in-depth interview was conducted with each participant, from which the information was analyzed. The results showed that young students consider consent as an essential part of the exercise of sexuality, while danger, violence and fear are not elements through which they represent it. On the other hand, there is influence of interpersonal relationships in the exercise of sexuality and autonomy with respect to the influence of peers in the exercise of sexuality in young university students. Likewise, it was identified that there is gender inequality and social roles, and different patterns appear in the way men and women express and experience the exercise of their sexuality.